Integrative Analysis of DiseaseLand Omics Database for Disease Signatures and Treatments: A Bipolar Case Study - Wu, Chun; Huang, Bevan E.; Chen, Guang; Lovenberg, Timothy W.; Pocalyko, David J.; Yao, Xiang (Frontiers in Genetics, 2019)
Transcriptomics technologies such as high-throughput next-generation sequencing and microarray platforms provide exciting opportunities for improving diagnosis and treatment of complex diseases. Transcriptomics studies often share similar hypotheses, but are carried out on different platforms, in different conditions, and with different analysis approaches. These factors, in addition to small sample sizes, can result in a lack of reproducibility. A clear understanding and unified picture of many complex diseases are still elusive, highlighting an urgent need to effectively integrate multiple transcriptomic studies for disease signatures. In collaboration with Omicsoft, we have integrated more than 3,000 high-quality transcriptomic datasets in oncology, immunology, neuroscience, cardiovascular and metabolic disease, and from both public and internal sources (DiseaseLand database). We established a systematic data integration and meta-analysis approach, which can be applied in multiple disease areas to create a unified picture of the disease signature and prioritize drug targets, pathways, and compounds. In this study, we provide an illustrative example using our approach to combine a total of 30 genome-wide gene expression studies for insight into the etiology of bipolar disorder. First, the studies were integrated by extracting raw FASTQ or CEL files, then undergoing the same procedures for preprocessing, normalization and statistical inference. Second, both p-value and effect size based meta-analysis algorithms were used to identify differentially expressed (DE) genes. The results revealed a total of 204 significantly DE (FDR < 0.05) genes in the prefrontal cortex. Among these were BDNF, VGF, WFS1, DUSP6, CRHBP, MAOA and RELN, which have previously been implicated in bipolar disorder. Finally, pathway enrichment analysis revealed a role for GPCR, MAPK, immune and Reelin pathways. The ability to robustly combine and synthesize the information from multiple studies enables a more powerful understanding of this complex disease.